The anti-angiogenic and anti-proliferative activity of n-benzoyl-3-phenyl isoserine derivative containing 1,2,3-triazole and quinoline rings - Nawar Raad Hussein; Hayder B. Sahib; Zahraa Sabbar Omran (PLoS ONE, 2026)
One of the biggest causes of death globally is cancer, which develops tumors characterized by angiogenesis and excessive cell proliferation. Cancer treatments targeting these pathways, especially those involving vascular endothelial growth factor, have had encouraging results. This study examined the anti-angiogenic and anti-proliferative properties of a phenyl isoserine derivative compound. The ex vivo anti-angiogenic activity was examined by rat aorta ring (RAR) and in vivo chorioallantoic membrane (CAM) assays. The in vitro anti-proliferative properties of the compound were analyzed utilizing Human umbilical vein endothelial (HUVEC), colon cancer, and breast cancer cell lines. Quantitative real-time PCR was used to measure gene expression of vascular endothelial growth factor receptor 2 ( VEGFR-2 ) gene. An evaluation was conducted on the compound’s SwissADME profile, molecular docking, and molecular dynamics simulations against the VEGFR-2 receptor. The phenyl isoserine derivative demonstrated significant anti-angiogenic activity in both the RAR and CAM assays, with a half-maximal inhibitory Concentration (IC 50 ) value of 18.91 μg/mL in the RAR assay. The compound also exhibited anti-proliferative effects against HUVEC, colon cancer, and breast cancer cells, with IC 50 values of 68.85, 124.75, and 112.31 μg/mL, respectively. The results of the Real-Time PCR test showed that at a concentration of 200 μg/mL, there was a significant decrease in the expression of the VEGFR-2 gene in Kaposi’s Sarcoma (KS) cells. The compound exhibited membrane permeability and dispersion, as expected based on the SwissADME profile, with a consensus log P o/w value of 3.14, while also indicating potential cytochrome P450 enzyme inhibition and poor water solubility ( Log Sw value: −8.34). Molecular docking (MD) studies revealed a higher PLP fitness score (91.496) for the compound compared to axitinib (78.748), suggesting a favorable binding to VEGFR-2. However, axitinib demonstrated a more negative binding energy (−14.548 kcal/mol vs. −7.715 kcal/mol), reflecting stronger energetic stabilization under docking conditions. Molecular dynamics simulations showed that ligand exhibits stable binding and induces greater structural stabilization of the target protein compared to axitinib, suggesting its potential as a more effective VEGFR-2 inhibitor. The phenyl isoserine derivative was found to have a potent inhibitory effect on angiogenesis and VEGFR-2 gene activity, indicating it could be a promising candidate for anti-cancer medicine.